On the Effect of Correlated Sways on Generalized Misalignment Fading for Terrestrial FSO Links - Ruben Boluda-Ruiz; Antonio Garcia-Zambrana; Beatriz Castillo-Vazquez; Carmen Castillo-Vazquez (IEEE Photonics Journal, 2017)
Terrestrial free-space optical (FSO) links are severely damaged by both atmospheric turbulence and misalignment errors. Generally, the optic community models misalignment by considering two different axes, i.e., the horizontal displacement and the elevation, as independent Gaussian random variables (RVs), whose probability density function is the well-known Beckmann distribution in the general case. In the current paper, we generalize this previous approach by misalignments with correlated sways since both the horizontal displacement and the elevation are not necessarily uncorrelated RVs in potential FSO applications. A statistical pointing error model is proposed, where not only is the laser beam width, detector size, and the effect of nonzero boresight and different jitter variances for each axes taken into account, but the effect of correlated sways is also taken into account. The proposed statistical model is used to evaluate the outage performance over gamma–gamma atmospheric turbulence channels. It is shown that the effect of correlation can only affect the coding gain when atmospheric turbulent is the dominant effect, while outage diversity is strongly dependent on correlation when pointing error is the dominant effect. Hence, correlation cannot be ignored in FSO systems. Simulation results are further included to confirm the analytical results.